2021
DOI: 10.1101/2021.06.04.447168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning The Knowledge: How London Taxi Drivers Build Their Cognitive Map of London

Abstract: Licenced London taxi drivers have been found to show changes in the grey matter density of their hippocampus over the course of training and decades of navigation in London (UK). This has been linked to their learning and using of the Knowledge of London, the names and layout of over 26,000 streets and thousands of points of interest in London. Here we examined the process of how this knowledge is acquired and we detail key steps that include: systematic study of maps, travel on selected overlapping routes, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Individual variation in such skill is not something an app on a mobile device can easily aid our understanding of. It will be important in future work to explore the links between the skill of highly expert navigators such as London taxi drivers (Griesbauer, Manley, Wiener, & Spiers, 2021; Maguire et al., 2006; Spiers & Maguire 2008). Moreover, it would be beneficial to understand how navigation performance in Sea Hero Quest relates to other spatial and nonspatial performance, given evidence that spatial navigation may be distinct from performance on more object‐based spatial tasks (Malanchini et al., 2020), nonspatial association memory (Ngo, Weisberg, Newcombe, & Olson, 2016), or autobiographical memory (Fan, Abdi, & Levine, 2021).…”
Section: Development Of a Worldwide Virtual Assessment Of Navigation ...mentioning
confidence: 99%
“…Individual variation in such skill is not something an app on a mobile device can easily aid our understanding of. It will be important in future work to explore the links between the skill of highly expert navigators such as London taxi drivers (Griesbauer, Manley, Wiener, & Spiers, 2021; Maguire et al., 2006; Spiers & Maguire 2008). Moreover, it would be beneficial to understand how navigation performance in Sea Hero Quest relates to other spatial and nonspatial performance, given evidence that spatial navigation may be distinct from performance on more object‐based spatial tasks (Malanchini et al., 2020), nonspatial association memory (Ngo, Weisberg, Newcombe, & Olson, 2016), or autobiographical memory (Fan, Abdi, & Levine, 2021).…”
Section: Development Of a Worldwide Virtual Assessment Of Navigation ...mentioning
confidence: 99%
“…Particularly illuminating could be the work on a parallel form of navigational skill in expert drivers: London cabbies (Spiers and Maguire, 2006 , 2007 ; Griesbauer et al, 2021 ). While vehicle dynamics, performance measures, and environment scale/3D complexity are different in these two domains of expertise, the design of the human memory system is the same, and therefore many of the computational problems and strategies may be the same.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis that follows builds on the interpretation of perceptual-cognitive skills in race driving in Lappi ( 2018 ), which was based on analyzing domain expert knowledge, elicited from content analysis of technical training literature and fitted into the McRuer hierarchy (cf. also the related analysis of expert knowledge through verbal protocol elicitation in London taxi drivers in Griesbauer et al, 2021 ). It was found that one standard way for racing drivers to describe the track is in terms of reference points ( Figure 3 ; see e.g., Code, 1983 , 1986 ).…”
Section: Navigation Guidance and Control: A Cognitive Hierarchymentioning
confidence: 99%
“…Taxi drivers were chosen because they are trained on the 'Knowledge of London' (e.g. TFL (n.d.)), which requires them to learn the entire London street network in order to navigate flexibly between places without consulting additional navigation aids (see Griesbauer et al, 2021). Years of training and extensive experience driving a taxi ensure exceptional familiarity within streets and districts in the six-mile area around Charing Cross station (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge consists of a profound knowledge of the street network, the street names, the location of places of interest and precise driving instructions (e.g. TFL, n.d.;Lordan, 2018;Electronic Blue Book, 2019;Griesbauer et al, 2021). As a result, licensed London taxi drivers daily navigate across sections of the ∼56,000 streets that form London (OS MasterMap Integrated Transport Network, 2018) without relying on any physical navigation aids.…”
Section: Introductionmentioning
confidence: 99%